Pengembangan Pembuatan Gula Tumbu Mutu I Melalui Metode Fosfatasi Dalam Skala Usaha Mikro - Semaarang, F. Sri Nugraheni Setiawati (Fakultas Teknik, Universitas Diponegoro Semarang), A. Sutowo (Teknis, 2015)
Tumbu sugar (brown sugar cane) is sugar produced from sugar cane moulding tumbu done traditionally by small scala industrty of brown sugar cane. Because there is no touch technology, the brown sugar cane low quality (second grade). Improving the quality of brown sugar cane be first quality have done through sulfitation method, but the main obstacle is sulphurous acid (H2SO3) is not available on the market, should produce in the laboratory. Then do the upgrading through fosfatation or method, used phosphoricacid that is readily availablein the market. In this first year MP3EI research, to develop a method of making brown sugar cane through fosfatation and analyze financial feasibility tobe implemented in small scala industry of brown sugar cane, but on this occasion no financial studies. The procedure is as follows: (1) the results ofthe milling of sugar cane juice is filtered dirty, discarded fiber(2) clean juice is heated in the open pan large capacity of 80-100 kg at a temperature of 55oâ65oC, (3) mixed with calcium oxide to be pH8.0 then added phosphoric acid to neutral pH7.0 and boiled, (4) put a separator vessel and stirred until the dirt settles, (5) clean juice then matured or heated in a openÂ  pan until at 100o C, (6) mature juice or liguor is poured into the mold, to solidify into brown sugar (tumbu sugar). The resulting brown sugar quality was analyzed by: (1) water content, (2) the sucrose content, (3) glucose content, (4) color, and (5) the weight of brown sugar cane and sugar cane juice ratio. The first year research obtained brown sugar cane first quality that feasible produced in small scale bisnis.Keywords: mould sugar, brown sugar cane, granulated sugar, vacuum packaging, apropriate technology